Desain Lembar Kerja Siswa Materi Sistem Persamaan Dua Variabel Berorientasi Etnomatematika - Drajat Friansyah; Maria Luthfiana (Jurnal Pendidikan Matematika:Judika Education, 2018)
This study aims to explain the steps in designing teaching materials in the form of Ethnomatematics-oriented worksheet on SPLDV material. The method used by the author in designing teaching materials is part or two of the initial stages of the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. The results of the study, the concept of ethnomatematics that can be integrated into the form of worksheets, namely, the unit of calculation in the sale and purchase transactions in traditional markets in the form of "secanting and" padembuk ", in addition to the typical Lubuklinggau batik motif in the form of durian motifs. Ethnomatematics context becomes the starting point in the learning process presented in the worksheet on the SPLDV material, so that mathematics learning can be more meaningful. Conclusion, quality Mathematics learning must be supported by various aspects, one of the main aspects is professional teachers who are able to utilize various learning resources and develop teaching materials (LKS) by utilizing the daily cultural context (ethnomatematics) experienced by students, thus the process occurs meaningful mathematics learning and growing awareness of students to appreciate local wisdom and culture in this case the culture of the city of Lubuklinggau. Keyword: Etnomatematika, SPLDV